Developers' Immunity Rights in Debt Payment Deferrals for Legal Certainty: Hak Imunitas Pengembang dalam Penundaan Kewajiban Pembayaran Utang untuk Kepastian Hukum - Heng, Richard Jemiel; Adam, Richard C. (Indonesian Journal of Law and Economics Review, 2025)
General background: The property sector, as a key pillar of Indonesia’s national economy, frequently encounters complex legal disputes between developers and consumers, particularly regarding debt obligations. Specific background: The Debt Payment Obligation Deferral (PKPU) mechanism under Law No. 37 of 2004 is designed to ensure legal certainty in debt restructuring. However, the requirement of simple evidence often complicates its application in property-related disputes. The Supreme Court addressed this through Circular Letter (SEMA) No. 3 of 2023, which effectively excludes developers from PKPU eligibility. Knowledge gap: Despite this policy’s practical significance, limited research has analyzed its normative legality and procedural implications. Aims: This study examines the legal nature of developers’ procedural immunity and the juridical consequences of PKPU revocation at the cassation level. Results: Findings reveal that the immunity arises from judicial activism that transfers dispute resolution from commercial to general civil courts and that PKPU revocation has a retroactive effect (restitutio in integrum), nullifying all related settlements. Novelty: The research introduces a conceptualization of procedural immunity in insolvency law, reflecting judicial policy intervention beyond legislative text. Implications: The study underscores the urgency of legislative reform to define simple proof criteria and to establish adaptive dispute resolution mechanisms for the property sector. Highlights: Establishes procedural immunity for developers through SEMA No. 3 of 2023. Highlights retroactive legal effects of PKPU revocation by the Supreme Court. Urges legislative reform to clarify simple proof standards in insolvency law. Keywords: Immunity Rights, Developers, PKPU, Legal Certainty, Judicial Activism